Development of four quadrant operation of DC to DC converter using single phase matrix converter - Rahimi Baharom; Abdul Muin Awang (Institute of Advanced Engineering and Science, 2019)
Single-Phase Matrix Converter (SPMC) is an advanced circuit topology that offer advantages such as the capability to regenerate energy back to the input, sinusoidal input and output current and a manageable input current displacement factor. By considering the opportunity of an advanced SPMC topology, further exploration on DC to DC operation is proposed. The four-quadrant operation of switching algorithm was developed to control the SPMC circuit. The voltage and current profile of each quadrant was investigated to validate the proposed switching control algorithm. As part of four quadrants DC to DC operation, the safe commutation switching algorithm was also developed in order to solve the commutation problem due to the used of an inductive load. The pulse width modulation (PWM) techniques was utilized to synthesize the output of the proposed converter. Results from MATLAB/Simulink are presented to validate the proposed circuit operation.